Colin Spencer: British Food. An extraordinary thousand years of history - Jaine, Tom (Petits Propos Culinaires, 2024)
Colin Spencer: British Food. An extraordinary thousand years of history: Grub Street, 2002: ISBN 1904010164: 400pp, h/b, £25.00.